2014
DOI: 10.7314/apjcp.2014.15.15.6263
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Thoracic Radiotherapy in Limited Stage Small Cell Lung Cancer: Results of Early Versus Late Irradiation from a Single Institution in Turkey

Abstract: Background: It is standard treatment to combine chemotherapy (CT) and thoracic radiotherapy (TRT) in treating patients with limited stage small cell lung cancer (LS-SCLC). However, optimal timing of TRT is unclear. We here evaluated the survival impact of early versus late TRT in patients with LS-SCLC. Materials and Methods: Follow-up was retrospectively analyzed for seventy consecutive LS-SCLC patients who had successfully completed chemo-TRT between January 2006 and January 2012. Patients received TRT after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
0
10
1
Order By: Relevance
“…These results suggest that RT is effective for the patients who do not shown a good response to CT despite the different reported results in the literature (5,31). The response rates to CT for SCLC were 60-95% in many studies (6,4,10,5). However, the total response rate to CT was 45% in our study because these patients were sent from other clinics after disease progression or bad results of CT.…”
Section: Discussioncontrasting
confidence: 47%
See 3 more Smart Citations
“…These results suggest that RT is effective for the patients who do not shown a good response to CT despite the different reported results in the literature (5,31). The response rates to CT for SCLC were 60-95% in many studies (6,4,10,5). However, the total response rate to CT was 45% in our study because these patients were sent from other clinics after disease progression or bad results of CT.…”
Section: Discussioncontrasting
confidence: 47%
“…The partial response rate increased to 53.7% post RT, while it was 25.92% pre RT. These results suggest that RT is effective for the patients who do not shown a good response to CT despite the different reported results in the literature (5,31). The response rates to CT for SCLC were 60-95% in many studies (6,4,10,5).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…One study showed that late TRT appeared to be superior to early TRT in terms of complete response and OS in patients with LS-SCLC. 20 In our study, concurrent CRT showed a trend toward improving the complete response rate, PFS and OS, but there was no significant difference between sequential group and concurrent group. For N3 LS-SCLC patients, systemic therapy plays a more important role compared with N0-2 patients.…”
Section: Discussionmentioning
confidence: 45%